2019
DOI: 10.1186/s12957-019-1653-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacological thromboprophylaxis and disease-stage on postoperative bleeding following colorectal cancer surgery

Abstract: Background Pharmacological thromboprophylaxis after colorectal cancer (CRC) surgery is internationally recommended for venous thromboembolism (VTE) prevention. The aim of this retrospective study was to evaluate the risk factors of postoperative bleeding after elective surgery for patients with primary CRC receiving pharmacological thromboprophylaxis of fondaparinux or enoxaparin. Methods We experienced consecutive 266 patients who underwent elective surgery for CRC dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…This may be due to a higher likelihood of patients with an increased baseline risk for VTE to receive prophylactic therapy, although this was not investigated in this study. However, hematoma rates were similar in the extended postoperative enoxaparin group compared with the entire MBR group ( P = 0.767), findings consistent with those of the 2014 study by Vedovati et al 15 and the 2019 study by Ohta et al, 16 which were prospective studies investigating extended postoperative thromboprophylaxis in colorectal surgery patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This may be due to a higher likelihood of patients with an increased baseline risk for VTE to receive prophylactic therapy, although this was not investigated in this study. However, hematoma rates were similar in the extended postoperative enoxaparin group compared with the entire MBR group ( P = 0.767), findings consistent with those of the 2014 study by Vedovati et al 15 and the 2019 study by Ohta et al, 16 which were prospective studies investigating extended postoperative thromboprophylaxis in colorectal surgery patients.…”
Section: Discussionsupporting
confidence: 82%
“…The benefits of extended VTE prophylaxis were first documented in colorectal surgery patients with multiple studies corroborating the results of the initial studies. 15 , 16 Improved outcomes with extended postoperative VTE prophylaxis have also been reported in urology in patients undergoing radical cystectomy, 17 in surgical oncology (oncologic liver surgery), 18 pancreatic surgery, 19 and oncologic gynecologic surgery. 20 , 21 Since these studies were published, many plastic surgeons have adopted extended postoperative VTE prophylaxis into their clinical protocols.…”
Section: Introductionmentioning
confidence: 91%
“…It has been found that thromboprophylaxis can reduce the risk of VTE in inpatients of internal medicine and surgery [ 30 ], and another resent study showed that continuing aspirin can also protect patients with high thromboembolic risk from VTE without increasing bleeding complications during the perioperative period [ 31 ]. Meanwhile, Ohta H. reported that fondaparinux administration appeared to be risk factors for postoperative bleeding in patients after colorectal cancer surgery [ 32 ]. Therefore, it is necessary to evaluate the bleeding risk and benefits before perioperative antithrombotic therapy carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is an important method of the treatment for early and middle stage tumors, and bleeding is often one of the most common complications of surgery (20). The complication of massive hemorrhage caused by surgery often endangers the life of patients, and needs timely hemostasis treatment (21)(22)(23)(24).…”
Section: Surgical Bleedingmentioning
confidence: 99%